Annona muricata (Soursop) on Hyperuricemia: an ANCOVA meta-analysis of controlled clinical trials. - Salim, Jonathan; Rahardja, Theodorus Samuel; Fatmawati, Dede; Madeline, Abigail (Australian Journal of Herbal & Naturopathic Medicine, 2025)
Background Annona muricata (soursop) is rich in vitamins and flavonoids that reportedly benefit humans. However, there is a scarcity of clinical studies that confirm these benefits in humans. Phenolic compounds and xanthine oxidase inhibitors reduce serum uric acid (SUA) production, accumulation, and renal excretion of SUA. Objectives Exploring the effects of soursop-containing preparations on SUA levels in individuals with hyperuricemia. Methods We analysed controlled clinical trials filtered from PubMed, the New England Journal of Medicine, PubMed Central, Cochrane, and citation searches using specific keywords. We investigated all studies conducted between 2017 and 2023 that included control groups and pre- and post-intervention measurements. The risk of bias was assessed for the non-randomised intervention studies and modified Jadad scores were used to measure the quality of each included study. The mean difference (MD) and heterogeneity were calculated using the Hartung-Knapp-adjusted random effects model for the analysis of covariance in the Recovered Effect Estimates Meta-Analysis using the metafor package in R. Results This novel meta-analysis included 15 studies with 937 participants aged 20-90 years. Most participants consumed preparations containing soursop at least once per week. Soursop significantly reduced SUA (MD: -1.14[-1.82 to -0.45], p=0.0031; I-squared = 98.03%, p<0.0001). However, this reduction was not statistically significant for preparations containing only soursop leaves (MD: -1.15[-2.73 to 0.43], p=0.1130; I-squared=95.81%, p<0.0001). Conclusion Intake of soursop-containing preparations is beneficial for individuals with high uric acid levels, particularly those with limited access, resistance or allergies to uric acid medications.